The Time is Ripe for Leadership Development: New Brunswick Vice-Principals Strive and Thrive Through Saturday Morning Participatory Action Research Seminars - Hamm, Lyle; Smith-Ellis, Shari; Cole, Tina; Kinney, Krysta; Garner, Andrea; Hartnett, Katharine; Razavi, Zeinab (The Canadian Journal of Action Research)

(untitled) (Canadian Association of Action Research in Education, 2025)
This paper describes a participatory action research project that was delivered on Saturday mornings to vice-principals (VPs) in two Anglophone school districts in the province of New Brunswick, Canada, in 2022 and 2023. The project was set up as an invitational five-part seminar series that was grounded in educational theory and leadership standards in Atlantic Canada. Forty-three VPs participated in the seminars offering the researcher/seminar leaders a deep look into their complex working lives. Data was gathered through a World Café activity, seminar observations, pre- and post- surveys, and exit interviews. Several themes were constructed by the research team and given back to the VPs for their consideration and reflection. Final seminars focused on topics and strategies that supported the VPs in their leadership development.